Analisis Kinerja Anggaran Belanja Pada PTN BLU X Tahun Anggaran 2021-2023 - Wulandari, Ratna; Surbakti, Lidya Primta (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
In managing the budget, it is crucial to conduct budget performance measurement or analysis, which involves assessing and measuring the implementation or realization of the budget. This study presents an original analysis of PTN X, a State University with BLU (Public Service Agency) status under the Ministry of Education, Culture, Research, and Technology. The BLU status provides flexibility in budget management. Therefore, the purpose of this research is to analyze the budget performance of PTN X as a basis for evaluation to improve quality. In this study, the authors use a descriptive quantitative method, with the research object being the budget performance of PTN X from 2021 to 2023. The data analysis techniques employed include several expenditure analysis calculations, namely 1) Variance Analysis, 2) Growth Analysis, 3) Compatibility Analysis, and 4) Efficiency Analysis. The Financial Expenditure Performance of PTN X, as seen from the Variance Analysis, falls into the good category or Favourable Variance. From the Growth Analysis perspective, there was no expenditure growth observed in 2022; however, there was expenditure growth in 2023. The Compatibility Analysis revealed an imbalance between operational and capital expenditures in 2021. In contrast, in 2022 and 2023, the balance between operational and capital expenditures can be considered stable. From the Expenditure Efficiency Analysis, it was found that the budget management of PTN X was inefficient during the years 2021-2023.